Rotating AdS3 × S3 and dyonic strings from 3-dimensions - Nihat Sadik Deger; Ceren Ayse Deral; Aritra Saha; Özgür Sarıoğlu (Journal of High Energy Physics)
Abstract We make a general Killing spinor analysis of a particular D = 3, N = 4 gauged supergravity that comes from a consistent S3 reduction of D = 6, N = (1, 0) supergravity coupled to a single chiral tensor multiplet. We then focus on its supersymmetric solutions with a null Killing vector and find three new ones. Two of these, namely the null warped AdS3 (also known as the Schrödinger spacetime) and the charged domain wall solutions, admit non-trivial gauge fields which give rise to rotating solutions in 6-dimensions. The uplift of the first one produces an interesting AdS3 × S3 background with a non-trivial rotation in the U(1) fiber direction of the S3 which retains the Schrödinger scale invariance that the seed solution has. The second one leads to the well-known rotating dyonic string solution. Finally, the uplift of the third one, which is a domain wall solution with no gauge fields, results in a distribution of dyonic strings.